'n Krygsteoretiese evaluering van die militêre optrede van generaal JH (Koos) de la Rey ter voorbereiding van en tydens die slag te Tweebosch-De Klipdrift, 7 Maart 1902 - Raath, Andries (Faculty of the Humanities, University of the Free State, 2011)
In this article an assessment is made of the military operations of General JH de la Rey during his preparations for the conflict and the military tactics employed during the battle of Tweebosch-De Klipdrift. The application of the criteria for determining the relative success of war operations enables us to conclude that the outcome of the battle was due to a number of principles operating in De la Rey’s favour. De la Rey’s successful application of these principles enabled him to score a significant success at Tweebosch-De Klipdrift the speed with which he massed his men at the crucial points of the conflict; his ability to stick to the objective identified; his seizing of the initiative and maintaining it; the unity of command he maintained throughout; his ability to keep his plans clear and simple; the element of surprise operating in his favour, and the fact that he allocated and applied his forces economically.
Keywords: De la Rey, Jacobus Herculaas; Tweebosch-De Klipdrift; Anglo-Boer War